MEDIASTINAL KAPOSIFORM HEMANGIOENDOTHELIOMA: BRIEF REVIEW OF THE LITERATURE WITH THE ADDITION OF A NEW CASE - Đurićić, Prim. Dr sc Slavisa; Sarajlija, Adrijan; Djokic, Dragomir; Simic, Radoje (Scripta Medica, 2020)
Kaposiform hemangioendothelioma (KHE) is a rare, locally invasive, vascular tumor, which is commonly associated with Kasabach-Merritt phenomenon (KMP). We present a case of a five-month-old female infant admitted for dyspnea, stridor, and skin hematoma. Computerized tomography of the chest showed a tumor mass occupying mediastinum and most of the left hemithorax, while laboratory analysis revealed thrombocytopenia and consumption coagulopathy. Histology of tumor biopsy was characteristic of KHE with a component of tufted angioma. Corticosteroid treatment initially induced a reduction in tumor size, but progression occurred 4 weeks later and led to a fatal outcome despite additional chemotherapy. After a literature search, we found only 18 cases of mediastinal KHE published so far, with death occurring in 21% of patients. In our case, several risk factors for adverse outcome were present: onset of disease in early infancy, a large volume of the tumor, mediastinal location, KMP, and partial response to therapy.
Keywords: kaposiform hemangioendothelioma; Kasabach-Merritt phenomenon; mediastinum; infant